Effect of adopting proactive work behaviors on achieving strategic entrepreneurship (Entrepreneurship Journal for Finance and Business, 2022)
Research aim to test effect of adopting proactive work behaviors in achieving strategic entrepreneurship. As research was applied in Directorate of Civil Status, Passports and Residence to test research hypotheses through a questionnaire prepared for this purpose. Research sample included (220) respondents intentionally, represented by (directors, heads of departments, directors of divisions, and unit officials in the directorate), research problem was represented in intellectual questions that describe a reality in which (proactive work behaviors and strategic entrepreneurship) are integrated, the most prominent of which was “Does the adoption of proactive work behaviors affect achievement of strategic entrepreneurship”. The research problem was manifested in the poor quality of services provided to members of society and its reliance on the electronic signal to accomplish most of the tasks of providing daily services to individuals or institutions alike. Importance of field research was evident in that it was applied in government security sector, which performs service security activity, which is one of important sectors because of its impact on the security and social aspects of the country. A set of statistical methods were used, the most important of which is the Pearson correlation coefficient by using (SPSS V.23) and structural equation modeling by using (Amos V.20). Research reached a set of conclusions, including presence of awareness among sample members about research variables, and that adoption of proactive work behaviors will achieve strategic entrepreneurship in directorate of research community. Research recommended a number of recommendations, including need to strengthen proactive behaviors to support excellence in providing services to members of Iraqi society and its residents, as an essential feature for sustainability of entrepreneurship of the Directorate, research community strategically.